LPS-Induced Systemic Inflammation Caused mPOA-FSH/LH Disturbance and Impaired Testicular Function - Shen, Peilei; Ji, Shuqin; Li, Xulin; Yang, Qingning; Xu, Bingxian; Wong, Chris Kong Chu; Wang, Liping; Li, Lei (Frontiers in Endocrinology, 2022)
Male reproductive function is key to the continuation of species and is under sophisticated regulation, challenged by various stressors including inflammation. In the lipopolysaccharide (LPS) intraperitoneal injection-induced acute systemic inflammation, male fecundity was compromised with decreased testosterone level, damaged spermatogenesis, and downregulations of testicular gene expression levels involved in steroidogenesis regulation and blood–testis barrier. It is also noteworthy that the testis is more sensitive to acute stress caused by LPS-induced systemic inflammation. LPS treatment resulted in lower testicular gene expression levels of steroidogenic acute regulatory protein, cholesterol side-chain cleavage enzyme, and cytochrome P450 family 11 subfamily B member 1 after LPS treatment, while no such decrease was found in the adrenal gland. In parallel to the significant decreases in testicular intercellular adhesion molecule 1, tight junction protein 1, and gap junction alpha-1 protein gene expression with LPS treatment, no decrease was found in the epididymis. In the brain, LPS treatment caused higher medial preoptic area (mPOA) activation in the hypothalamus, which is accompanied by elevated blood follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, suggesting a disturbed hypothalamic–pituitary–gonad axis function. Besides mPOA, brain c-fos mapping and quantitative analysis demonstrated a broad activation of brain nuclei by LPS, including the anterior cingulate cortex, lateral septum, paraventricular nucleus of the hypothalamus, basolateral amygdala, ventral tegmental area, lateral habenular nucleus, locus coeruleus, Barrington’s nucleus, and the nucleus of the solitary tract, accompanied by abnormal animal behavior. Our data showed that LPS-induced inflammation caused not only local testicular damage but also a systemic disturbance at the brain–testis axis level.